Neuronal Precursor Cell Expressed Developmentally Down Regulated 4 (NEDD4) Gene Polymorphism Contributes to Keloid Development in Egyptian Population - Farag AGA; Khaled HN; Hammam MA; Elshaib ME; Tayel NR; Hommos SEI; El Gayed EMA (Dove Medical Press, 2020)
Azza GA Farag,1 Hesham N Khaled,1 Mostafa A Hammam,1 Mustafa Elsayed Elshaib,2 Nermin Reda Tayel,3 Sahar Elsoudy Ibrahim Hommos,4 Eman Masoud Abd El Gayed5 1Dermatology, Andrology and STDs Department, Faculty of Medicine, Menoufia University, Shibin El Kom, Egypt; 2Faculty of Medicine, Menoufia University, Shibin El Kom, Egypt; 3Department of Molecular Diagnostics and Therapeutics, Genetic Engineering Biotechnology Research Institute, Sadat City, Egypt; 4Dermatology Department, Elsherouk General Hospital, Cairo, Egypt; 5Medical Biochemistry and Molecular Biology Department, Faculty of Medicine, Menoufia University, Shibin El Kom, EgyptCorrespondence: Azza GA FaragDermatology, Andrology and STDs, Faculty of Medicine, Menouﬁa University, Shibin El Kom 32511, EgyptTel +20 109 778 7204Fax +20 2482 226 454Email azzagaber92@yahoo.comBackground: Keloids represent chronic fibroproliferative skin disorders in which there is deposition of extracellular components, especially type 1 collagen, fibronectin and elastin, in excessive amounts. NEDD4 is associated with fibrosis found in abnormal wound healing through increased fibroblast proliferation and regulation of type 1 collagen expression. The exact etiology of keloid formation is undefined, but the role of genetic factors was demonstrated.Objective: To investigate the polymorphism of the NEDD4 gene rs8032158 in a sample of Egyptian patients who have keloids.Methods: The current case–control study was conducted in 160 unrelated subjects; 100 keloid patients and 60 ages and sex coincided with apparently healthy controls. All subjects underwent a complete history, and weight and length were measured to calculate body mass index (BMI). The Vancouver Scar Scale (VSS) was used to assess keloid severity. An analysis of the polymorphism of the NEDD4 gene rs8032158 T/C was performed using taqman allelic discrimination (real-time PCR).Results: The rs8032158 CC genotype was observed significantly in keloid patients and increased the risk of keloid development by approximately 2 times (p = 0.003, OR = 1.80). The C allele significantly increased the risk of keloid development by approximately 2 times (P = 0.002, OR = 2.08). The carriers of the CC genotype were significantly associated with severe keloid form and with the highest VSS values.Conclusion: The polymorphism of the NEDD4 gene rs8032158 could participate in the formation of keloids in the Egyptian population. The NEDD4 rs8032158 CC genotype may have a role in keloid severity.Keywords: NEDD4, keloid, gene polymorphism